A Contribution to Resource-Aware Architectures for Humanoid Robots - Kröhnert, Manfred (Karlsruhe Series on Humanoid Robotics, 2017)
The goal of this work is to provide building blocks for resource-aware robot architectures. The topic of these blocks are data-driven generation of context-sensitive resource models, prediction of future resource utilizations, and resource-aware computer vision and motion planning algorithms. The implementation of these algorithms is based on resource-aware concepts and methodologies originating from the Transregional Collaborative Research Center ""Invasive Computing"" (SFB/TR 89).